Customers' Opinions on Reasons for Using Online Banking: Experience of Customers in Tanzania - Sikira, Richard (International Journal of Scientific Research and Management (IJSRM), 2021)
Information technology has revolutionalised the banking industry with enormous benefits. However, there have been mixed perceptions on preferring online banking to traditional banking. These perceptions usually change over time because of deliberate efforts done by stakeholders. This study aimed to determine the opinions of customers on the reasons for using online banking services. In conducting this research, the study opted to use a case study research design. The study employed 60 CRDB Bank customers as its sample size. The study collected its data through primary data, by using a semi-structured questionnaire that allowed the collection of quantitative and qualitative data. The researcher employed content analysis through descriptions for qualitative data and simple descriptive statistics analysis through frequencies and percentages for quantitative data. The study found that most respondents (customers) use online banking because it saves time, offers instant feedback, is reliable, and is secure and convenient. The study recommends more awareness and understanding of online banking services to users to enjoy the enormous benefits of online banking services. Furthermore, customer support must be improved and ensure keeping promises related to solving customers' problems. The study recommends categorically further research on the contribution of mobile money to the reduction of income poverty